Intentional Tech : Principles to Guide the Use of Educational Technology in College Teaching - Bruff, Derek (Book collections on Project MUSE., 2019)
"Chalkboards and projectors are familiar tools for most college faculty, but when new technologies become available, instructors aren't always sure how to integrate them into their teaching in meaningful ways. For faculty interested in supporting student learning, determining what's possible and what's useful can be challenging in the changing landscape of technology. Arguing that teaching and learning goals should drive instructors' technology use, not the other way around, Intentional Tech explores seven research-based principles for matching technology to pedagogy. Through stories of instructors who creatively and effectively use educational technology, author Derek Bruff approaches technology not by asking 'How to?' but by posing a more fundamental question: 'Why?'"--Publisher's description.